PLASMA CHOLESTEROL AND LIPOPROTEINS PROFILE IN HEALTHY SAUDI PERSONS - Abdulrahman, Mohamed A.; M. Hassan, Mahmoud; A. Ibrahim, Ali (Gezira Journal of Health Sciences, 2008)
Objectives :  to study the differences in the concentrations of plasma total cholesterol (TC), triglycerides (TG), LDL-C and HDL-C in normal healthy Saudi persons according to gender, age and lifestyle. Methods : For all tested research group the blood was drawn after an overnight fasting period (12-14hrs) using heparinized tubes. Enzymatic colorimetric method were used for analyse and the mean values and standard deviation for all parameters were obtained. Results : The results showed lower T.C, TG and LDL-C levels through childhood group (<1-14 years) for both sexes with no significant differences between rural and urban areas. With the exception of HDL-C, other parameters increased with increasing of age for both sexes, indicating the effect of diet and lifestyle. However, HDL-C decreases during adolescence reaching its lowest level at the age of 40 years. It remains constant up to the age of 55 years in both sexes, and then it started to rise to a constant level at later ages. This coincided with significant increase of total cholesterol, triglycerides and LDL-C that approached the dangerous levels in both city males and females above 40 years of age. Conclusion : This study suggests that differences in dietary habits and lifestyle were much more effective in the adult groups who lived in cities at an age above 40 years to be at risk of coronary heart disease. This was in line with the significantly higher levels of bad cholesterol and lower levels of the good one.